Achievement of Sustainable Development Goals. Report for 2023. Wroclaw University of Economics and Business - Drelich-Skulska, Bogusława [Kierownik merytoryczny raportu] (Publishing House of Wroclaw University of Economics and Business, 2024)
[The report is devoted to the achievement of sustainable development goals at Wroclaw University of Economics and Business in 2023. The document shows what SD actions are taken at the university with a special emphasis on the following goals: quality education, economic growth and decent work, innovation, industry, infrastructure, sustainable cities and communities as well as climate action.] nota autora
s. 67
Keywords: sustainable development; higher education; education quality; economic growth; sustainable cities